RESEARCH ON THE TEACHING METHODS OF JAPANESE LANGUAGE - Rakhimova Khumora Fakhriddin qizi (Scholar Express Journal, 2024)
The article discusses the current state of Japanese language learning in the world. As a result of the study, a period of decrease in the number of institutions where the Japanese language is studied was identified in Uzbekistan. Having analyzed statistical data regarding the number of such institutions, it was revealed that such a situation was uncharacteristic for the same period in other countries of Eastern Europe. Current problems of teaching and new developments in the field of teaching the Japanese language are considered. An example of a lesson using modern methods of teaching the Japanese language is given.
Keywords: Japanese language; modern teaching methods; realities